Book Review of Multilingualism and Translanguaging in Chinese Language Classrooms by Wang Danping - Haojun Guo (Canadian Society for Studies in Education, 2022)
The book review first summarizes the main content of the five chapters in the book Multilingualism and Translanguaging in Chinese Language Classrooms written by Danping Wang in 2019. It emphasizes the knowledge contribution of the book but also points out what can be done in the future. This book review may interest those teachers, educators or students who teach Chinese as a second language or have an interest in multilingualism/bilingualism.